Locus Standi in the Law of Administrative Process in Tax Matters - León Pinedo, Silvia (2014)
The article begins by recognizing that the Administrative Process in Peru is full jurisdiction, protects the legal situations in addition to control the legality of the administrative acts. Then the author examines the Tax Administration, specifically if SUNAT has active legitimacy to sue in a Contentious Administrative Process against the decision issued by the Tax Court that revoked or annulled their administrative acts, concluding that it does not have legitimacy but, exceptionally, according to article 157 of the Tax Code, can sue when SUNAT demonstrates that RTFs are not according to the parameters of article 10 of the General Administrative Procedure Act, confirming that the causal most used by SUNAT are those of the numeral 1 and 2, referred to the resolutions which cause serious disability vice, which, according to the author, is not the same as a different interpretative approach. Finally, the author concludes that for tax issues does not apply the second paragraph of Article 13 of the Law on Administrative Process; apply the article 157 of the Tax Code, as the special rule.